1992
DOI: 10.1182/blood.v80.8.2012.bloodjournal8082012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of granulocyte survival and programmed cell death by cytokines and bacterial products

Abstract: Mature circulating polymorphonuclear cells (PMN) have the shortest half- life among leukocytes and undergo rapid programmed cell death in vitro. In this study, we have examined the possibility that inflammatory signals (cytokines and bacterial products) can regulate PMN survival. PMN in culture were found to rapidly die, with percentages of survival at 24, 48, 72, and 96 hours of 97.3% +/- 1.9%, 36.8% +/- 5.3%, 14.5% +/- 3.1%, and 4.2% +/- 2.9%, respectively (mean +/- SE of 20 different donors). PMN incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
325
3
8

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(345 citation statements)
references
References 0 publications
9
325
3
8
Order By: Relevance
“…The antiapopotic effects of MSC were of similar magnitude and duration as those reported by other investigators upon neutrophil incubation with various cytokines, including IL‐1β, TNF, IL‐6, interferon‐γ, granulocyte colony‐stimulating factor, and granulocyte macrophage–colony‐stimulating factor [49, 50]. In analogy to our findings, cytokine‐driven rescue of neutrophils from apoptosis occurred through rapid modulation of Bax and MCL‐1 [47].…”
Section: Discussionsupporting
confidence: 88%
“…The antiapopotic effects of MSC were of similar magnitude and duration as those reported by other investigators upon neutrophil incubation with various cytokines, including IL‐1β, TNF, IL‐6, interferon‐γ, granulocyte colony‐stimulating factor, and granulocyte macrophage–colony‐stimulating factor [49, 50]. In analogy to our findings, cytokine‐driven rescue of neutrophils from apoptosis occurred through rapid modulation of Bax and MCL‐1 [47].…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have shown that when granulocytes are stored in solutions containing G–CSF or dexamethasone, apoptosis is delayed, and cell viability and function can be maintained for more than 48 hours 11,12 . These studies differed from the current study in several ways: donors were not given G–CSF or dexamethasone, but these agents were added to the granulocytes during storage; granulocytes were separated from RBCs, platelets, and lymphocytes; and granulocytes were stored in culture media at a much lower cell concentration.…”
Section: Discussionmentioning
confidence: 56%
“…When granulocytes are incubated with G–CSF or dexamethasone, apoptosis is delayed and in vitro survival prolonged 11,12 . When granulocyte donors are given G–CSF plus dexamethosone, in vivo granulocyte survival is prolonged 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in the desired correction of both parameters. A possible explanation is that recommencing G‐CSF increased the number of circulating neutrophils (Demetri & Griffin, 1991) and delayed neutrophil apoptosis (Colotta et al ., 1992) thereby allowing the maternal antibody to be mopped up.…”
Section: Discussionmentioning
confidence: 99%